2019
DOI: 10.3390/ijerph16101737
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Different Heavy Metals Dissolved in Drinking Water

Abstract: Water pollution is a major threat to public health worldwide. The health risks of ingesting trace elements in drinking water were assessed in the provinces of Punjab and Khyber Pakhtunkhwa, Pakistan. Eight trace elements were measured in drinking water, using Inductively Coupled Plasma Mass Spectrometry (ICP-MS), and compared with permissible limits established by the World Health Organization (WHO) and the Pakistan Environmental Protection Agency (Pak EPA). In addition, health risk indicators such as the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…The use of correlation analysis in groundwater studies to uncover the relationship between various parameters to show their source and pathways is reported in many works of literature (Varol and Davraz 2014;Hussain 2019;McGrorya 2020). In this study, the correlations between the various parameters are shown in Table 4.…”
Section: Correlation Analysismentioning
confidence: 95%
“…The use of correlation analysis in groundwater studies to uncover the relationship between various parameters to show their source and pathways is reported in many works of literature (Varol and Davraz 2014;Hussain 2019;McGrorya 2020). In this study, the correlations between the various parameters are shown in Table 4.…”
Section: Correlation Analysismentioning
confidence: 95%
“…Samples for total PTE analyses were preserved with drops of ultra-pure conc. 65% HNO 3 (pH < 2) to eliminate microbial activity (Hussain et al, 2019). Groundwater pH was determined on site for unacidified samples using a calibrated multi-parameter tester 35 (Eutech Instruments, USA).…”
Section: Sampling and Sample Analysesmentioning
confidence: 99%
“…Their findings indicate heavy metals in all springs and a possible noncancer risk from nitrates in adults and children. Similarly, Hussain et al [17] estimated the health risk from heavy metals in drinking water and reported that Lahore, Vehari, Jhang, and Multan, Pakistan, exceed the safe limits of the health risk index for metals such as Cr, Ni, and As.…”
Section: Introductionmentioning
confidence: 99%